EXERCISE INTENSITY ARE FREEZING TIME OF BLOOD IN RATS WITH WHITE SMOKE EXPOSURE - Lalu Win (Jurnal Kesehatan Prima, 2016)
Abstract: Cigarette smoke is a heterogeneous aerosols from burning tobacco and wrapping. Each cigarette contains over 4000 chemicals, 400 of them are poisonous and approximately 43 of which are carcinogenic. Smoking is closely linked with lung cancer, emphysema and chronic bronchitis. In addition, smoking is also a risk factor for atherosclerosis. One of the new risk factors are not fully known is homocysteine. Smoking is one of the factors that can lead to increased plasma homocysteine levels. The purpose of this study was to know the influence of moderate intensity exercise on blood clotting time in rats that pajan smoke. The design of the study is a posttest only control group design. The sample is 30 rats (Rattusnorvegicus) adult males over the age of 2 to 3 months with severe badan160-175gr, with a healthy physical condition. Rats were randomly divided into 3 tiem: The control group that was not given exposure to cigarette smoke and exercise just put in shallow water when swimming K2. The group that was given exposure to cigarette smoke without exercise Mice given exposure to cigarette smoke as much as 2 cigarettes / day using a pump smooking, by placing the mice in a glass box. Putting rats in shallow water when swimming K2. The group that was given exposure to cigarette smoke and exercise for 30 minutes after being given the exposure to cigarette smoke, mice direnangkan for 80% of the time swimming ability 6% maximum load weight. The results showed that exposure to cigarette smoke shortening clotting time in rats. Moderate intensity exercise prevented shortening clotting time in rats with exposure to cigarette smoke. Conclusions from the study of moderate intensity exercise on blood clotting time in rats with exposure to cigarette smoke.